The Arrival and Development of Islam in Rejang Lebong Regency - Lukman Asha (Institut Agama Islam Negeri (IAIN) Curup, 2016)
The arrival of Islam in the 7th century to the world is considered by historians as the builder of a new world with new thinking, new ideals, new culture and civilization. For more than fourteen centuries since the Prophet Muhammad spread the new teachings in theology monotheistic, areas of individual life, the field of public life, and the state, Islamic civilization has been widespread ranging from Spanish territory to the citadel of China, from the valley of the river Volga in Russia to Southeast Asia, and even later almost to the whole world, including Indonesia, Sumatra and Bengkulu. Islam was spread in various ways, such as through activites of trade, agriculture, education, establishment of a mosque, and getting marriage so that Islam has spread throughout the corners of the country in ground water included in Rejang Lebong Regency. Keywords: Islam, Rejang Lebong